KOMPARASI KULINER PADA RESTORAN ARAB DI JAKARTA (STUDI KASUS RESTORAN AWTAR DAN RESTORAN AL JAZEERAH) - Annisa, Safira (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2023)
This article aims to reveal the comparison or differences in spices and menus and presentation at the Awtar restaurant and the Al Jazeerah restaurant. This research is a qualitative research regarding the comparison or differences in spices and menus and presentation at Awtar restaurants and Al Jazeerah restaurants. The data and information obtained are analyzed by means of data reduction, presentation and drawing conclusions. This research uses data collection methods carried out by means of observation, interviews. In the observation activity, the researcher was a participant - observer, and interviews were conducted to gather information from the managers of the Awtar and Al Jazeerah restaurants. The research results show that there are many differences between the Awtar restaurant and the Al Jazeerah restaurant, starting from the spices and menu and food presentation. Every Arab restaurant has its own way of mixing and cooking food or drinks, such as the Awtar restaurant, which has different menu and presentation preferences from the Al Jazeerah restaurant.